Case report: Traumatic median neuropathy in the distal forearm after massage therapy - Suh, Mi Rim; Song, Jun Hyeong; Park, Yongbum; Lee, Seok Hyeon; Ahn, Jaeki (Frontiers in Neurology, 2022)
Median nerve damage caused by trauma is rare, especially after massage therapy. There have been no reports of median neuropathy in the distal forearm following massage therapy. A 61-year-old man developed paresthesia and numbness in the right hand after two sessions of massage therapy. Electrophysiologic studies, ultrasound, and magnetic resonance imaging were used to localize and confirm the median nerve lesion in the distal forearm. Ultrasound-guided perineural steroid injection and oral pregabalin were administered. At the 1-month follow-up, more than 80% of the sensory symptoms had resolved, and the results of the sensory nerve conduction study and ultrasound showed improvement. Although massage-induced mononeuropathy is uncommon, massage therapy should be performed carefully to avoid complications.